Genotypic and bio-agronomical characterization of an early Sicilian landrace of globe artichoke - Mauro, Rosario Paolo; Portis, Ezio; Lanteri, Sergio; Mauromicale, Giovanni (Euphytica, 2012)
In Sicily, the increasing use of exotic globe artichoke germplasm is eroding the presence of autochthonous landraces, including the long established ‘Violetto di Sicilia’. Ten clones have emerged from a clonal selection programme in this landrace, and here we describe the variation that they capture both at the level of AFLP-based genotype and phenotypically with respect to key productivity traits, on the basis of two seasons of field evaluation. The clonal selections yielded, on average, 8.9 heads per plant (equivalent to a fresh weight yield of 1.28 kg). Two clones yielded particularly well in both growing seasons (10.6 heads, equivalent to 1.46 kg per plant), while another pair produced particularly large heads (on average 165 g) and a high receptacle incidence (on average 19.3 g 100 g −1 fresh weight). Both the number of days to first harvest and the quantity of head dry matter were subject to a significant degree of ‘clone × year’ interaction. Yield, the number of heads per plant and receptacle incidence were associated with a moderate (0.30–0.53) broad sense heritability, indicating that these traits could be successfully improved by phenotype-based clonal selection. AFLP fingerprinting was able to discriminate between all the clones, based on only three primer combinations. A principal component analysis based on the AFLP fingerprints was used to compare the selected clones with a set of individuals chosen on the basis of maximum genetic diversity. This comparison suggested that the new clone set was representative of the genetic variation present in ‘Violetto di Sicilia’, because the diversity captured by the two sets was largely overlapping, confirming the possibility of carrying out clonal selection in this globe artichoke landrace without compromising its preservation in situ .